The impact of cultural differences on the performance of post-acquisition integration in cross-border M&A: The roles of classification of culture and firms’ internal capabilities - Wang, Lin-Qi (2017)
This paper pursues the idea that the relationship between cultural differences and post-acquisition integration may be not as uniform as many studies suggest. By examining two cases of Chinese enterprises in cross-border M&A, this study is marked out from existing studies in the following three respects.